CORPORATE SOCIAL RESPONSIBILITY: PROSPECTS AND OPPORTUNITIES AMONG SMALL AND MEDIUM BUSINESS IN UKRAINE - О. В. Жмай (Ринкова економіка: сучасна теорія і практика управління)
The purpose of this article is studying of modern CSR practices among small and medium business in Ukraine. During the investigation the chronological, comparative, statistical and tabular methods were used. The features of corporate social responsibility, typical for small and mediumsized businesses (SMB), were analyzed. The state and practice of corporate social responsibility among SMBs in Ukraine were described. The materials of the article could be used by small and medium business’s owners. One of the main messages that small and medium businesses may understand, is the following: corporate social responsibility – it is a concept which does not necessarily imply additional financial (or other) costs or coercive measures. CSR policy, above all, must be inscribed in the business strategy, as it relates to enterprise development planning, improve its competitiveness and cost optimization.